IDENTIFICATION OF CAUSES, AND PREVENTION OF DEFECT STRUCTURE AND REPAIR METHODS IN THE IMPLEMENTATION OF HIGH-RISE BUILDING CONCRETE CONSTRUCTION (Case Study of The Newton 2 Apartment Project) - Salsabila Aisyah Naviasih; Abdul Rochman (Jurnal Ekonomi, 2023)
Concrete is one of the materials that is often used in various construction projects. This is due to several advantages possessed by concrete, including when viewed in terms of cost efficiency, concrete has cheaper work and maintenance costs compared to steel, besides that when compared in terms of flexibility, concrete will be more easily formed as desired depending on the shape and strength of the formwork. In the implementation of construction projects, several problems are often encountered, including damage to the concrete structure, which weakens the building structure. The use of concrete in building construction also requires continuous evaluation and repair or reinforcement of the structure so that the concrete can function again at a good performance.